(2R, 6R)-hydroxynorketamine targeting the basolateral amygdala regulates fear memory. (1st March 2023) - Xu, Yuanyuan; Yu, Zhenfei; Chen, Si; Li, Zhenlong; Long, Xiting; Chen, Mengxu; Lee, Chau-Shoun; Peng, Hsien-Yu; Lin, Tzer-Bin; Hsieh, Ming-Chun; Lai, Cheng-Yuan; Chou, Dylan
Abstract: (2 R, 6 R )-Hydroxynorketamine (HNK), a ketamine metabolite, has been proposed as an ideal next-generation antidepressant due to its rapid-acting and long-lasting antidepression-relevant actions. Interestingly, recent studies have shown that (2 R, 6 R )-HNK may have diverse impacts on memory formation. However, its effect on fear memory extinction is still unknown. In the present study, we assessed the effects of (2 R, 6 R )-HNK on synaptic transmission and plasticity in the basolateral amygdala (BLA) and explored its actions on auditory fear memory extinction. Adult male C57BL/6J mice were used in this study. The extracellular electrophysiological recording was conducted to assay synaptic transmission and plasticity. The auditory fear conditioning paradigm was performed to test fear extinction. The results showed that (2 R, 6 R )-HNK at 30 mg/kg increased the number of c-fos-positive cells in the BLA. Moreover, (2 R, 6 R )-HNK enhanced the induction and maintenance of long-term potentiation (LTP) in the BLA in a dose-dependent manner (at 1, 10, and 30 mg/kg). In addition, (2 R, 6 R )-HNK at 30 mg/kg and directly slice perfusion of (2 R, 6 R )-HNK enhanced BLA synaptic transmission. Furthermore, intra-BLA application and systemic administration of (2 R, 6 R )-HNK reduced the retrieval of recent fear memory and decreased the retrieval of remote fear memory. Both local and systemic (2 R, 6 R )-HNK also inhibited the spontaneous recovery of remote fear memory. Taken together, these results indicated that (2 R, 6 R )-HNK could regulate BLA synaptic transmission and plasticity and act through the BLA to modulate fear memory. The results revealed that (2 R, 6 R )-HNK may be a potential drug to treat posttraumatic stress disorder (PTSD) patients. Highlights: Systemic (2 R, 6 R )-HNK increased intracellular signaling activity in the BLA. Systemic (2 R, 6 R )-HNK elevated synaptic transmission and plasticity in the BLA. Local and systemic (2 R, 6 R )-HNK attenuated recent and remote fear memories. Local and systemic (2 R, 6 R )-HNK inhibited spontaneous recovery.